Quality of energy intake in Malaysian adolescents: prevalence, characteristics, determinants and impact of implausible reporters - Mohamed S Zulfarina; Razinah Sharif; Ahmad Mohd Sharkawi; Sabarul Afian Mokhtar; Ahmad Nazrun Shuid; Isa Naina-Mohamed (Cambridge University Press, 2023)
Abstract Objective: Misreporting of energy intake (EI) in nutritional epidemiology is common and even severe among adolescents. Thus, the current study aims to examine the presence, bias and impact introduced by implausible reporters. Design: Cross-sectional. Setting: Central and eastern regions of Peninsular Malaysia. Participants: A stratified random sampling was employed to select 917 secondary school-going adolescents (aged 15-17 years). Results: The prevalence of under-reporters was 17·4 %, while no over-reporters were identified. Under-reporters had higher body composition and lower dietary intakes (except for vitamin C, Cr and Fl) compared with plausible reporters (P < 0·05). Adolescents with overweight and obesity had a higher odds of under-reporting compared with under-/normal weight adolescents (P < 0·001). In model 3, the highest regression coefficient (R 2 = 0·404, P < 0·001) was obtained after adjusting for reporting status. Conclusions: Overweight and obese adolescents were more likely to under-report their food intake and consequently affect nutrient intakes estimates. Future analyses that include nutrient intake data should adjust for reporting status so that the impact of misreporting on study outcomes can be conceded and consequently improve the accuracy of dietary-related results.